Pemikiran Baru Pandangan Teologi: Substantif, Relasional, dan Fungsional Tentang Gambar Rupa Allah - Dewi, Ester Yunita; Baskoro, Paulus Kunto (Jurnal Teologi Berita Hidup, 2025)
Theological study of the image of God helps to understand the two words, words that are not different in meaning, but reinforce each other. The topic of the image and likeness of God has produced three popular views, namely the substantial, relational and functional views. Each of these three views has advantages and disadvantages. The aim of the research is to present a third view in a balanced way and to develop new thinking apart from conducting comparative and evaluation studies. Methode search as methode kualitatif deskritif. The findings of this study indicate that: First, the image of God is a fully Man. The results of the research on the word image and likeness in Genesis 1:26-31, 5:1-3 and 9:6 prove that the use of the words "image" and "likeness" are not separate or distinct terms. In essence, the meaning of the words "image" and "likeness" is the same. Second, the image of God in Genesis 1:26, is man was created to be God's representative, that is, to rule over His creation, to rule in the sense of carrying out God's mandate. Third, the image of God requires God's Atonement. The history of human life on earth tells that humans violate God's word and cause humans to sin. Humans need redemption to be able to live obediently and be able to carry out God's mandate of "power." The complete restoration of the original man as even more like the heavenly body and that of Christ will take place in the eternities. Fourth, further research. The researcher realizes that the results of this study are still incomplete because it opens up opportunities for further research.